Investigation of ribociclib, abemaciclib and palbociclib resistance in ER+ breast cancer cells reveal potential therapeutic opportunities - Mashael Algethami; Ahmed Shoqafi; Ayat Lashen; Shatha Alqahtani; Jake Spicer; Ahmad ALtayyar; Çağla Tosun; Jennie N Jeyapalan; Nigel P. Mongan; Victoria James; Emad A. Rakha; Srinivasan Madhusudan (Scientific Reports)
Abstract The cyclin-dependent kinase 4/6 inhibitor (CDK4/6i) ribociclib, abemaciclib, and palbociclib have transformed outcomes in patients with ER+ /HER2 − advanced breast cancer (BC). However, most patients eventually progress, and therapeutic options beyond CDK4/6i are an area of ongoing investigation. Here, we generated and evaluated ribociclib, abemaciclib, and palbociclib-resistant BCs. MCF7 and T47D (ER+ /HER2−) cells were chronically treated with increasing doses of ribociclib (R), abemaciclib (A), or palbociclib (P) over 8 months (0-600 nM). CDK4/6i-resistant cell lines (MCF7rR, MCF7rA, MCF7rP, T47DrR, T47DrA, and T47DrP) were isolated and evaluated for their aggressive phenotypes, cross-resistance, transcriptomic changes, and sensitivity to volasertib (PLK1 inhibitor) and barasertib (AukB inhibitor). Immunohistochemical evaluation of CDK4, CDK6, and p53 (n = 1005) and transcriptomic evaluation of AukB and PLK1 were performed in 5031 clinical breast cancers. MCF7rR, MCF7rA, MCF7rP, T47DrR, T47DrA, and T47DrP cells manifested aggressive phenotypes such as increased spheroid formation, invasion, proliferation, and progression through the G1/S phase of the cell cycle despite CDK4/6i treatment, increased resistance to apoptosis, and cross-resistance to other CDK4/6i. Transcriptomic analysis revealed the enrichment of distinct pathways in resistant cells, particularly the upregulation of cell cycle regulatory genes such as PLK1, AukB, CDKN2B and TGFβ. PLK1 or AukB overexpressing resistant cells were sensitive to volasertib (PLK1 inhibitor) and barasertib (AukB inhibitor) therapy, which was associated with G2/M cell cycle arrest and increased apoptosis. We conclude that cell cycle upregulation leading to G2/M progression is a key route for CDK4/6i resistance. AukB or PLK1 inhibitors that block G2/M phase could be a promising strategy.